Peran Agama Dalam Masyarakat Multikultural - Siti Rohmaniah (Pascasarjana IAIN Metro, 2018)
Multiculturalism is the recognition that different cultures can exist in the same environment and benefit each other. Multicultural societies have become a special character of the nation more specifically in Indonesian society, and have been discussed in various activities, seminars, discussion forums and in academic environment. Multicultural society is a society consisting of several kinds of cultural communities with all its advantages, with little difference in the conception of the world, a system of meaning, values, forms of social organization, history, customs and habits The role of religion will constructively make religious ties more stringent, often even exceeding the bondage of blood and nasab or ductility relationships. Then because of religion, a community or society will live in unified harmony and peace and unity. Conversely, destructively, religion also has destructive power, destroys unity and can even break the bond of unity. It makes a conflict with a religious background difficult to predict the end. The religion has the potential to generate an internal and external conflicts that ultimately can harm the community itself.